2006
DOI: 10.1017/s1368980006009712
|View full text |Cite
|
Sign up to set email alerts
|

Age-related variations in flavonoid intake and sources in the Australian population

Abstract: Objective: To estimate flavonoid intake in the Australian population. Design: Flavonoid consumption was estimated from 24-hour recall data and apparent consumption data using US Department of Agriculture flavonoid composition data. Subjects: The National Nutrition Survey 1995 assessed dietary intake (24-hour recall) in a representative sample (n ¼ 13 858) of the Australian population aged 2 years and over. Results: Analysis of the 24-hour recall data indicated an average adult intake (. 18 years) of 454 mg day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
(20 reference statements)
4
38
5
Order By: Relevance
“…Previously, the intake profiles of flavonoid groups according to age were determined in a representative sample of the Australian population (19). This and another previous study (20) reported variations in flavonoid intake according to age.…”
Section: Introductionmentioning
confidence: 91%
“…Previously, the intake profiles of flavonoid groups according to age were determined in a representative sample of the Australian population (19). This and another previous study (20) reported variations in flavonoid intake according to age.…”
Section: Introductionmentioning
confidence: 91%
“…The main sources of flavonoids were tea, onions, grapefruit, and tofu [42]. In a study of 13,858 Australians, total flavonoid consumption was 454 mg/day in adults, with the most important sources being tea (76% of intake) and oranges [43]. Lower flavonoid intakes of approximately 200 mg/day were reported in Europe and the United States.…”
Section: Observational Studies On Flavonoids and Cardiovascular Diseasementioning
confidence: 99%
“…They are ubiquitously present in the green plant world and the human diet, such as in vegetables, fruits, and plant-derived beverages. An adult takes in approximately 200 mg of dietary flavonoids each day in the United States and 350 mg each day in Australia (Chun et al, 2007;Song et al, 2006;Johannot and Somerset, 2006). The cancer chemopreventive properties of dietary flavonoids have become an important topic of investigation; both dietary and synthetic flavonoids have been subjected to clinical trials (Thomasset et al, 2007 andBooth et al, 2006).…”
Section: Introductionmentioning
confidence: 99%